Rural Working-Class Males in Sweden and Reading: Processes for Re-appropriating Written Culture - Asplund, Stig-Börje; Goodson, Ivor (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
This article explores the intersection of place-based reading practices of rural working-class males and reading practices in school. Life story interviews have been conducted with six men in different ages (age 19-63) living in a rural region in Sweden, focusing on their reflections on their own relation to reading across a life span from the standpoint of the present. The analysis shows that there is a unique combination of factors at work when rural working-class men culturally re-appropriate written culture in ways that are sympathetic, and socially acceptable to a manual working-class culture. These factors include the processes of oralising and manualising and are often related to things learned in specific ancestral heartlands.